Do Lawyers Affect Grievance Arbitration Outcomes? The Newfoundland Experience - Thornicroft, Kenneth (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1994)
Unions and employers are no doubt aware that retaining legal counsel necessitates a more expensive and less expeditious grievance arbitration process. But if a party's prospects for success are enhanced by legal representation, the additional delay and expense may be justified. Does legal representation affect grievance outcomes? Most arbitrators are lawyers. Does an arbitrator's legal training affect the outcome of a grievance"! These, and other issues are examined in this study. The results suggest that legal representation does not affect grievance outcomes; nor do lawyer-arbitrators decide cases any differently than their lay colleagues.